2013
DOI: 10.1108/arla-06-2013-0069
|View full text |Cite
|
Sign up to set email alerts
|

What can Latin‐American entrepreneurs learn from Catalan gazelles?

Abstract: Purpose The purpose of this paper is to systematize the strategic capabilities of seven surviving industrial Catalan companies which were going through explosive growth in 1999. Design/methodology We use the comparative case studies method to draw on the common features among the seven in‐debt cases we built. We are well aware that the method of comparative case studies does not provide a sufficient base for bold generalizations. However, the qualitative approach adopted here allows for the first in‐depth lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…A recent study revealed that R&D activity contributes to the survival of young high-growth firms, also called gazelles (Andonova, Stoyanova, Valencia, & Juliao-Rossi, 2013). Therefore, gazelles stimulate economic growth in developed countries BERR, 2008;Henrekson & Johansson, 2010).…”
Section: High-potential Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that R&D activity contributes to the survival of young high-growth firms, also called gazelles (Andonova, Stoyanova, Valencia, & Juliao-Rossi, 2013). Therefore, gazelles stimulate economic growth in developed countries BERR, 2008;Henrekson & Johansson, 2010).…”
Section: High-potential Entrepreneurshipmentioning
confidence: 99%
“…Studies on entrepreneurial ecosystem often associate high‐potential firms with innovation, increased productivity, and local employment growth (Napier & Hansen, ; World Economic Forum, ; Collombelli, Krafft, & Quatraro, ). A recent study revealed that R&D activity contributes to the survival of young high‐growth firms, also called gazelles (Andonova, Stoyanova, Valencia, & Juliao‐Rossi, ). Therefore, gazelles stimulate economic growth in developed countries (Acs et al, ; BERR, ; Henrekson & Johansson, ).…”
Section: High‐potential Entrepreneurshipmentioning
confidence: 99%
“…In addition, less developed countries present higher rates of entrepreneurial activity than developed (Fernández-Serrano and Liñán, 2014). However, these rates do not represent the growth benefits mentioned throughout the literature, among other reasons because most new ventures in Latin America have a low orientation to the international markets (Andonova et al , 2013), given their low competitiveness and their weak value-added (Amorós et al , 2016). To propose alternatives to face international and other challenges for the entrepreneurship in the region, it is necessary to know the state of the research in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Ante la pregunta de por qué sobreviven y terminan convirtiéndose en exitosas determinadas nuevas empresas, son muchos los estudios que, apoyándose en la trc, destacan que son aquellas capaces de identificar y adquirir recursos y capacidades muy valiosos para los primeros años de vida en un entorno tan dinámico como en el que nos encontramos (Andonova et al, 2013;Mingo, 2013). Si nos centramos en la dimensión 'individuo', el interés en los factores intrín-secos asociados al emprendedor deriva de la supuesta conexión con la supervivencia y crecimiento de las empresas, lo que sugiere que, para atravesar las diferentes fases de desarrollo de un negocio, es necesario disponer de un nivel mínimo suficiente en una serie de competencias.…”
Section: Contabilidad Y Finanzasunclassified